2018
DOI: 10.1002/adma.201805334
|View full text |Cite
|
Sign up to set email alerts
|

Lithiophilic 3D Nanoporous Nitrogen‐Doped Graphene for Dendrite‐Free and Ultrahigh‐Rate Lithium‐Metal Anodes

Abstract: discharge and charge. These problems cause early cell death, poor Coulombic efficiency (CE), rapid cycling capacity decay, and catastrophic thermal runaway. [9][10][11][12] To overcome the above thorny issues, extensive endeavors have been revived and a number of strategies have been proposed and practiced. For example, strengthening the solid electrolyte interphase (SEI) films by engineering liquid electrolytes with functional additives (LiNO 3 , Cs + , LiF, etc.) or employing solid electrolytes to prevent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(209 citation statements)
references
References 57 publications
(66 reference statements)
3
206
0
Order By: Relevance
“…But, the lack of suitable electrode materials strictly hinders the development of metal‐ion batteries. Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume expansion 80‐82,90,91‐96 . The strategy for the feasible nanostructured assembly of a three‐dimensional porous graphene/niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high‐rate capability at practical levels of mass loading.…”
Section: The Versatile Applications Of 2d Group‐iva Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the lack of suitable electrode materials strictly hinders the development of metal‐ion batteries. Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume expansion 80‐82,90,91‐96 . The strategy for the feasible nanostructured assembly of a three‐dimensional porous graphene/niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high‐rate capability at practical levels of mass loading.…”
Section: The Versatile Applications Of 2d Group‐iva Materialsmentioning
confidence: 99%
“…Graphene, a class of superior thermal and electrical conductors, can not only act as a conductive filler but also form the desirable nanocomposite electrode structures in conjunction with carbon nanotubes, transition metal oxides, and so forth to enhance ion infusion, electron transfer, and alleviate the volume [79] expansion. [80][81][82]90,[91][92][93][94][95][96] The strategy for the feasible nanostructured assembly of a three-dimensional porous graphene/ niobia (Nb 2 O 5 ) composite was applied by Sun et al 83 to prepare the 3D electrode architecture delivering high areal capacity and high-rate capability at practical levels of mass loading. Subsequently, Zhao et al 84 found that densely packed Li x M/graphene foils (M = Si, Sn, or Al) would serve as air-stable and freestanding anodes guaranteeing stable structures and exceptional cyclabilities ( Figure 10).…”
Section: Batteriesmentioning
confidence: 99%
“…Instead, the ex situ construction of an artificial protection layer on Li is a more versatile technique to obtain desired compositions and structures. Carbon materials and polymers are frequently employed to build physical layers for preventing dendrite penetration in Li anodes . The flexibility of these materials effectively accommodates volume fluctuation of the underlying anode upon Li plating/stripping…”
Section: Figurementioning
confidence: 99%
“…[2,[6][7][8][9][10][11] However, even with the aid of these interfacial layers, uniform deposition is difficult as it is dependent on a plethora of external factors including ion diffusion, screw dislocation of atoms, and the morphology of the electrode surface. [14][15][16][17][18][19][20][21][22][23][24][25] This specific technique offers several advantages: [26] 1) the porous structure reduces the local current density and ensures sufficient Li ion flux; 2) the porous 3D skeleton accommodates the volumetric change of the Li anode during the plating and stripping progress; 3) Li is deposited on the interior of the 3D matrices, but not directly on the surface of the electrode, thus prohibiting dendrite growth. [14][15][16][17][18][19][20][21][22][23][24][25] This specific technique offers several advantages: [26] 1) the porous structure reduces the local current density and ensures sufficient Li ion flux; 2) the porous 3D skeleton accommodates the volumetric change of the Li anode during the plating and stripping progress; 3) Li is deposited on the interior of the 3D matrices, but not directly on the surface of the electrode, thus prohibiting dendrite growth.…”
Section: Introductionmentioning
confidence: 99%